2014
DOI: 10.1016/s2214-109x(14)70310-9
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance for rheumatic heart disease in endemic regions: a systematic review and meta-analysis of prevalence among children and adolescents

Abstract: We included 37 populations in the systematic review and meta-analysis. The pooled prevalence of rheumatic heart disease detected by cardiac auscultation was 2·9 per 1000 people (95% CI 1·7-5·0) and by echocardiography it was 12·9 per 1000 people (8·9-18·6), with substantial heterogeneity between individual reports for both screening modalities (I² = 99·0% and 94·9%, respectively). We noted an association between social inequality expressed by the Gini coefficient and prevalence of rheumatic heart disease (p = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
141
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(159 citation statements)
references
References 43 publications
12
141
1
5
Order By: Relevance
“…6 There was no difference between men and women regarding their level of adherence, although an earlier study by Dorothy had revealed that men are more likely to be non-adherent compared to their female counterparts. 7 Whether the lack of significant factors reflects a true lack of association, a limited time to follow up, or rather, the effect of a small sample size is uncertain from these results. Most of the studies done on this topic have not analyzed for these patient factors, making it rather a complex area to discuss.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…6 There was no difference between men and women regarding their level of adherence, although an earlier study by Dorothy had revealed that men are more likely to be non-adherent compared to their female counterparts. 7 Whether the lack of significant factors reflects a true lack of association, a limited time to follow up, or rather, the effect of a small sample size is uncertain from these results. Most of the studies done on this topic have not analyzed for these patient factors, making it rather a complex area to discuss.…”
Section: Discussionmentioning
confidence: 95%
“…5 In addition, these sex differences might be stronger in adolescents and adults than in children. 5,7 Regular administration of antibiotics to children who have had rheumatic fever is effective in reducing the number of recurrences of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Children with no RHD at age 9-10 years are at risk of developing ARF later in adolescence. Age matters in terms of cumulative incidence of ARF and of the prevalence of RHD [7,25,29]. Acute rheumatic fever incidence was similar across in RHD and non-RHD groups.…”
Section: A Single Screening Point In Childhood May Prove Insufficientmentioning
confidence: 91%
“…Data on the natural history of subclinical RHD are lacking and some experts in the field have questioned the need for secondary prophylaxis, especially in those diagnosed as borderline RHD [11]. Since the landmark study that suggested echo-based screening as a possible option for disease-control [10], other groups have found that ultrasound-led diagnosis may be of interest, with higher sensitivity and specificity than auscultation [25]. To the best of our knowledge, three prospective studies assessing the prognostic significance of subclinical RHD are currently on going [26][27][28].…”
Section: Echo-screened Rhd Albeit Mild Persists Over Timementioning
confidence: 99%
“…3 The dramatic modifications in the 2015 Jones Criteria include: (1) acceptance of echocardiographic evidence of significant mitral and/or aortic valve regurgitation even in the absence of a typical murmur as evidence of carditis and (2) defining low-risk populations and those that are moderate to high risk for ARF and rheumatic heart disease (RHD) as well as establishing somewhat different Jones Criteria for these two different sets of populations. The latter change is designed to make it somewhat easier to diagnose ARF in those moderate to high-risk populations with substantially higher pretest probability for ARF on clinical presentation.…”
mentioning
confidence: 99%